Answer:
option A.) y-3 = 1/16 (x-2)^2
Explanation:
we know that
If the axis of symmetry is parallel to the y-axis, then we have a vertical parabola
The equation of a vertical parabola is equal to
![4p(y-k)=(x-h)^(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/db7135cg3sq9d2rqe890l4ty5xuvsvhiy6.png)
where
(h,k) is the vertex
In this problem we have
(h,k)=(2,3)
p=4
substitute
![4(4)(y-3)=4(4)(x-2)^(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/x0cfc3c99tcj42xico5g2npabwxun4m90s.png)